Experimental Analysis to Evaluate the Effect of Dynamic Absorber / M. Azhan Anuar...[et al.] - Anuar*, M. Azhan; A. Samat, Syafirah; Mat Isa, A.A. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Passive Dynamic Absorber (PDA) is a mechanical device used to tackle unwanted vibration resonance within the operational frequency of the system. Theoretically, resonance can be avoided if the excitation (operating) frequency is far away from the natural frequencies of the structures. Hence, it is important to identify the structural natural frequencies, to ensure this condition did not occur. In this study, an experimental main system is designed and fabricated and then, tested using Operational Modal Analysis (OMA) to obtain the natural frequency. PDAs are developed based on Dunkley Method (DM) and Randy Fox Method (RFM) and applied to the main vibrating system. Frequency Response Function (FRF) for both models is obtained using OMA and its effectiveness is evaluated. It is shown that the PDA reduces the magnitude of FRF of the main system at the selected resonance frequency and splitting it into two new resonance frequencies. Hence, it can be predicted that the vibration can be effectively suppressed at a specific frequency when the PDA is attached to the main system. This study enables verification of the effectiveness of dynamic absorber to tackle resonance problem. In future, these results will be helpful to evaluate the performance of PDA based on DM and RFM methods.